2013
DOI: 10.4314/agrosh.v12i2.5
|View full text |Cite
|
Sign up to set email alerts
|

Cowpea Reaction to Single and Mixed Viral Infection with Blackeye Cowpea Mosaic Virus and Cowpea Yellow Mosaic Virus

Abstract: Potted experiment was carried out in the screenhouse of the Crop Protection Department, Faculty of Agriculture, University of Ilorin, Nigeria to determine the yield reaction of cowpea to single and mixed viral infection with Blackeye Cowpea Mosaic Virus (BICMV) and Cowpea Yellow Mosaic Virus (CYMV) at different inoculation regimes. The experiment was laid out in a complete randomized block design (CRD). The two viral inoculums (BICMV and CYMV), were mechanically inoculated to cowpea plants, singly and in mixtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
(15 reference statements)
3
1
0
Order By: Relevance
“…Disease severity varied among the inoculated crop cultivars due to their different genetic make-up. The severity of infection increased over time in some cultivars, which is in agreement with the report of Aliyu et al (2012) when some cowpeas were inoculated with B1CMV. Roma Savanna cultivar of tomato, which had the lowest level of CMV incidence and also elicited the mildest symptoms of infection, was probably due to the presence of CMV tolerance genes.…”
Section: Discussionsupporting
confidence: 90%
“…Disease severity varied among the inoculated crop cultivars due to their different genetic make-up. The severity of infection increased over time in some cultivars, which is in agreement with the report of Aliyu et al (2012) when some cowpeas were inoculated with B1CMV. Roma Savanna cultivar of tomato, which had the lowest level of CMV incidence and also elicited the mildest symptoms of infection, was probably due to the presence of CMV tolerance genes.…”
Section: Discussionsupporting
confidence: 90%
“…Reduction in 100-seed weight was markedly impaired in FDRF7-57 as a consequence of infection which culminated in small sized and deformed seeds. This is consistent with the findings of Aliyu et al (2012) who reported significant reduction in seed weight of cowpea plants infected with BlCMV.…”
Section: Discussionsupporting
confidence: 93%
“…BICMV has been identified as one of the major viruses infecting cowpea. Apart from individual attack it is capable of causing synergistic disease complex in the presence of compatible plant virus (Aliyu et al, 2012). Presently, cultivation of resistant varieties is the most effective, sustainable and ecologically sound control strategy.…”
Section: Discussionmentioning
confidence: 99%
“…in the "Cream" landrace, resulting in small, malformed seeds. This is in line with the report by [29] who recorded a significant reduction in seed weight in cowpea plants infected with the CMV.…”
supporting
confidence: 93%